Utilization of clinical practice guidelines: a survey of Canadian pediatric physicians - Nasir, Fareeha; Nicholson, Katharine; Vandermeer, Ben; Kumar, Manoj; Robinson, Joan (International Journal of Medicine, 2014)
Background: It is not clear how physicians currently use clinical practice guidelines (CPGs).Objectives: The objective was to describe how Canadian pediatric residents and pediatricians use CPGs and to identify barriers to CPG use.Methods: Pediatric emergency physicians and general pediatricians in Edmonton and Ottawa and all Canadian pediatric residents were surveyed regarding patterns of use for CPGs and barriers to use.Â Results: Response rate was 178/847 (21%).Â The majority of responding residents (62%), emergency physicians (54%) and general pediatricians teaching more than 6 weeks annually on a clinical teaching unit (CTU) use CPGs at least monthly (55%) with less frequent use by pediatricians who teach 1 to 6 weeks on CTU (14%) or rarely/never teach on CTU (21%) (p<0.001). Canadian physicians are more likely to read Canadian Paediatric Society guidelines when they are published versus referring to them later when dealing with clinical problems while the opposite appears to be true for American Academy of Pediatrics guidelines. The most common barrier to use of guidelines is forgetting that a guideline exists for a specific problem. The majority of physicians access CPGs electronically and support development of web based tools to improve accessibility.Conclusions: Almost all pediatric residents, pediatric emergency physicians and general pediatricians sometimes refer to CPGs. General pediatricians teaching less than 6 weeks per year on CTUs are an important target population, as most use CPGs infrequently. Prompts that CPGs exist and accessible online summaries of CPGs appear to have potential for overcoming the barriers to use.